Mineralogy, geochemistry and the origin of high-phosphorus oolitic iron ores of Aswan, Egypt - Baioumy, H. (Elsevier B.V., 2017)
The Coniacian-Santonian high-phosphorus oolitic iron ore at Aswan area is one of the major iron ore deposits in Egypt. However, there are no reports on its geochemistry, which includes trace and rare earth elements evaluation. Texture, mineralogy and origin of phosphorus that represents the main impurity in these ore deposits have not been discussed in previous studies. In this investigation, iron ores from three localities were subjected to petrographic, mineralogical and geochemical analyses. The Aswan oolitic iron ores consist of uniform size ooids with snowball-like texture and tangentially arranged laminae of hematite and chamosite. The ores also possess detrital quartz, apatite and fine-grained ferruginous chamosite groundmass. In addition to Fe2O3, the studied iron ores show relatively high contents of SiO2 and Al2O3 due to the abundance of quartz and chamosite. P2O5 ranges from 0.3 to 3.4 wt. showing strong positive correlation with CaO and suggesting the occurrence of P mainly as apatite. X-ray diffraction analysis confirmed the occurrence of this apatite as hydroxyapatite. Under the optical microscope and scanning electron microscope, hydroxyapatite occurred as massive and structureless grains of undefined outlines and variable size (5–150 μm) inside the ooids and/or in the ferruginous groundmass. Among trace elements, V, Ba, Sr, Co, Zr, Y, Ni, Zn, and Cu occurred in relatively high concentrations (62–240 ppm) in comparison to other trace elements. Most of these trace elements exhibit positive correlations with SiO2, Al2O3, and TiO2 suggesting their occurrence in the detrital fraction which includes the clay minerals. ΣREE ranges between 129.5 and 617 ppm with strong positive correlations with P2O5 indicating the occurrence of REE in the apatite. Chondrite-normalized REE patterns showed LREE enrichment over HREE ((La/Yb)N = 2.3–5.4) and negative Eu anomalies (Eu/Eu* = 0.75–0.89). The oolitic texture of the studied ores forms as direct precipitation of iron-rich minerals from sea water in open space near the sediment-water interface by accretion of FeO, SiO2, and Al2O3 around suspended solid particles such as quartz and parts of broken ooliths. The fairly uniform size of the ooids reflects sorting due to the current action. The geochemistry of major and trace elements in the ores reflects their hydrogenous origin. The oolitic iron ores of the Timsha Formation represent a transgressive phase of the Tethys into southern Egypt during the Coniacian-Santonian between the non-marine Turonian Abu Agag and Santonian-Campanian Um Barmil formations. The abundance of detrital quartz, positive correlations between trace elements and TiO2 and Al2O3, and the abundance mudstone intervals within the iron ores supports the detrital source of Fe. This prediction is due to the weathering of adjacent land masses from Cambrian to late Cretaceous. The texture of the apatite and the REE patterns, which occurs entirely in the apatite, exhibits a pattern similar to those in the granite, thus suggesting a detrital origin of the hydroxyapatite that was probably derived from the Precambrian igneous rocks. Determining the mode of occurrence and grain size of hydroxyapatite assists in the maximum utilization of both physical and biological separation of apatite from the Aswan iron ores, and hence encourages the use of these ores as raw materials in the iron making industry. © 2016 Elsevier B.V.